Synthesis of 1-(2’,4’-Dichloro-5’-Fluorophenyl)-3-(3’-Hydroxy-4’-Methoxy-5’-aryl azo)- 2-Propene-1-one Disperse Azo Dyes Based on Chalcone and Their Application on Polyester Fibre - Patel, Vikram; Desai, Vikas (Asian Journal of Chemistry, 2012)
Some new azo disperse dyes 1-(2',4'-dichloro-5'-fluoro phenyl)-3-(3'-hydroxy-4'-methoxy-5'-aryl azo)-2-propene-1-one were synthesized and their dyeing performance on polyester fibre was assessed. These dyes were characterized by elemental ana1ysis; IR spectra and NMR spectra. The fastness properties of these dyes were evaluated by applying them on polyester fibre. The values of λmax, Rf, % exhaustion and dyeing behaviour, such as wash, light and rubbing fastness of prepared compounds, have been studied.